Síntese de nanopartículas de NaYF4:Yb3+:Er3+ para aplicações em sistemas fotovoltaicos - Garcia, Beatriz (2021)
Current technology in the production of photovoltaic energy uses a silicon-based material that absorbs solar radiation in the visible part of the electromagnetic spectrum. However, a fraction of the electromagnetic radiation emitted by the sun, which reaches the Earth's surface, is in the near infrared region and is not used in conventional photovoltaic systems. This feature encourages the study of processes of upconversion of energy (upconversion - absorption of infrared radiation with visible emission). The radiation emitted in this process can thus be absorbed by the active layer of the device, silicon or another material, thus increasing the efficiency of the system. One of the materials with great efficiency in the process of upconversion of energy is the pair of rare earths Ytterbium and Erbium. In this project, nanocrystals of sodium fluoride and yttrium doped with the rare earths ytterbium and erbium (NaYF4: Yb3 +: Er3 +) were synthesized by the thermal decomposition method via hot injection. The structural and optical characterization of the nanocrystals was carried out using the techniques of XRD, TEM, optical absorption and photoluminescence indicating monodisperse nanocrystals with average sizes of 32 nm and with good energy conversion rate. After synthesis and characterization, NaYF4: Yb3 +: Er3 +nanocrystals were inserted into the TiO2 mesoporous layer interface for the construction of the organicinorganic hybrid Perovskite photovoltaic system (CH3NH3PbI3). The active layer of CH3NH3PbI3 was synthesized using the one-step synthesis method using ethyl acetate anti-solvent. The layers of the devices were deposited in an open atmosphere and without strict humidity control. Thus, two sets of devices were prepared, the first set with devices without the inclusion of NaYF4:Yb 3+: Er3+ nanocrystals reference system, and a second set with the inclusion of nanocrystals in the TiO2 mesoporous layer interface, which, 81% increase in their efficiency.